Analisis Putusan Perkara Anak Pelaku Tindak Pidana Eksploitasi Secara Ekonomi Dan Seksual Terhadap Anak Secara Online (Studi Putusan No.6/Pid.Sus-Anak/2020/Pn.Pdg) - Ivandro Elpasya; Nelwitis Nelwitis; Riki Afrizal (Fakultas Hukum Universitas Andalas, 2023)
This paper is a case study with case number 6/Pid.Sus-Anak/2020/Pn.Pdg which has permanent legal force. In this decision, the child is the perpetrator of the crime of economic and sexual exploitation of children. Juridically in Article 70 of the SPPA Law, the personal circumstances of the child, or the circumstances at the time of the act or what happened later can be used as a basis for the judge's consideration not to impose imprisonment. However, in this decision the judge imposed a prison sentence on the child. The problem formulations discussed in this paper are: 1. How is the judge's consideration in imposing a criminal judgment against the child who is the perpetrator of the criminal offense of Economic and Sexual Exploitation of Children (Decision Number 6/Pid.Sus-Anak/2020/Pn.Pdg)? 2. Is the Judge's Decision Number 6/Pid.Sus-Anak/2020/Pn.Pdg. in accordance with the Purpose of Punishment of Children? The legal research method used is normative juridical with a problem approach, namely, case, statutory and conceptual approaches. This research is descriptive analytical, data collection techniques with document studies or literature studies. In the legal analysis of case settlement, according to the author, the child should not have been sentenced to imprisonment because first, the child had not previously committed a criminal offense, second, the child was cooperative and polite during the trial and the consequences of the incident hindered the child's growth and development. Judge Decision Number 2/Pid.Sus-Anak/2019/Pn.Pdg is not in accordance with the objectives of punishment in general, which are more precisely regulated in the SPPA Law because it emphasizes restitution to the original state rather than retaliation, and the use of imprisonment or detention as a last resort or as an ultimum remedium.